Features of Emotional Disorders in Students with Disorders of the Cardiovascular System - Alieva, T.; Burdun, N. (Psychiatry, Neurology and Medical Psychology, 2016)
In the article the features of the current state of emotional development disorders and psychological maladjustment of students with disabilities, diseases of the cardiovascular system. The study was conducted at Kharkov City Hospital in the Student Mental Health Center students. The study involved 153 students from cardiovascular diseases (78 students with disabilities who have congenital heart disease and 75 students with somatoform autonomic dysfunction). The main aspects of the study of disorders of adaptation of students with disability are the psycho-emotional state, motivational orientation of the individual, personal characteristics and quality of life. On the basis of these results has been developed and implemented a program of medical and psychological treatment for this group of patients.